A review of Peratophyga Warren, 1894 in China, with descriptions of two new species (Lepidoptera: Geometridae, Ennominae) - Jiang, Nan; Xue, Dayong; Han, Hongxiang (Zootaxa, 2012)
The genus Peratophyga Warren, 1894 in China is reviewed. Six species are recognized, of which P. crista sp. nov. and P. recta sp. nov. are described. P. hyalinata grata (Butler, 1879) is restored to specific rank as P. grata (Butler, 1879) stat. rev. P. grata totifasciata Wehrli, 1923 comb. nov. is proposed. P. xanthyala (Hampson, 1896) and P. grata grata (Butler, 1879) are newly recorded for China. Two species are transferred from Peratophyga to the genus Stegania Guenée, 1845: S. castaneostriata (Yazaki & Wang, 2004) comb. nov. and S. modesta (Yazaki & Wang, 2004) comb. nov. A key to Chinese Peratophyga and diagnoses for Chinese species are provided. Illustrations of external features and genitalia are presented.